Implementation Of Micro Finance Products With Mudharabah Contract At BMT NU Sejahtera Cilimus Kuningan - Wahyuni, Neneng; Fauzan, Arif; Firdaus, Dicky F. (International Conference on Islamic Economic (ICIE), 2023)
ABSTRACT Mudharabah is one of the contracts in the sharia economy that is able to accommodate financing activities for micro business actors. In fact data from the OJK, Mudharabah contracts are still classified as minority contracts in Indonesian Islamic financial institutions. This is because the process is considered more risky and difficult so it is less strategic when applied to financial institutions. Interestingly, one of the BMT operating in Kuningan, West Java, BMT NU Sejahtera carries a financing product with this profit sharing contract. Using qualitative research methods, the authors examine the implementation of Mudharabah contracts in this BMT. From the results of the study it was found that in practice of the contract, there are still things that are not in accordance with sharia principles, such as fixed monthly installment payments, collateral requirements and if the customer suffers a loss, payments are still made even though only the principal. This discrepancy with the Shari'a is understood as an attempt by the BMT to minimize risk. Hopefully in the future, all of Islamic financial institutions and the community can both understand fiqh muamalah so that the practice of contracts in Islamic economics can be carried out purely according to the Shari'a.